Consumers’ Preference and Perception of the Different Broiler Housing and Feeding Systems Among Staff and Students in a State University (Eskişehir Osmangazi University) - Canan Kop Bozbay (Turkish Journal of Agriculture: Food Science and Technology)
In this study, an investigation of the preference and perception of the different broiler housing and feeding systems among staff and students of Eskisehir Osmangazi University, Turkey was undertaken. A structured questionnaire was administered with a face-to-face to 790 randomly selected respondents [257 academic staff (academicians), 166 non-academic staff (worker with a secondary school national graduate diploma) and 367 undergraduate students (students)]. Most respondents preferred chicken (63.3%) and beef (32.0%) meats to fish meat (4.7%). The number of academicians preferred broiler meat (16.8%) was lower than those of students (52.6%) and workers (30.6%). There were significant differences among respondents in terms of preference and perception of different production sources of chicken meat. The proportion of academicians who preferred conventional broiler meat (68.2%) was higher than students (25.4%) and workers (6.4%). The impact of mediatic information (disinformation) about broiler meat relating to ingredients and/or feed additives used in broiler nutrition was higher on academics and students compared to workers. The results of the study indicated that as the level of education increases, the negative perception increased due to false media reports about chicken meat production and subsequently, the preference for chicken meat decreased.